Identification of chicken FSHR gene promoter and the correlations between polymorphisms and egg production in Chinese native hens. Issue 4 (23rd March 2019) - Li, Xiaopeng; Lu, Yinglin; Liu, Xiaofan; Xie, Xiaolei; Wang, Kun; Yu, Debing
Contents: Egg production is an important economic trait in poultry, and it is of great significance to study the key genes and functional SNPs that affect egg laying performance. Follicle‐stimulating hormone (FSH) plays an important physiological role in the reproductive performance of humans and animals by binding to its receptor (FSHR). Studies have shown that there are many transcriptional regulatory elements in the 5′ flanking region of the FSHR gene that interact with transcription factors to regulate FSHR transcription. In this study, DNA sequencing was used to identify SNPs in the FSHR promoter sequence in both Dongxiang and Suken chickens. To detect the activity of the chicken FSHR gene promoter, we analysed the characteristics of the sequence and constructed three deletion vectors. We confirmed that the region (−18/−544) was the core promoter. Furthermore, five polymorphisms, including a 200‐bp indel at −869, C−1684T, C−1608T, G−368A and T−238A, were detected in both the Dongxiang and Suken chickens. The age at first egg (AFE) for different genotype of −869 indel in Suken chicken was significantly different ( p  < 0.01). For SNP C−1684T in Dongxiang chickens, the CC genotype had higher egg number at 43 weeks of age (E43) than that of the TC genotype ( p  < 0.05). For SNP C−1684T in Suken chickens, the TC genotype had higher AFE than that of the CC genotype ( p  < 0.05). For SNP C−1608T in Suken chickens, the CC genotype had higher AFE than that of the TC genotype ( p  < 0.05). For SNP G−368A in Suken chickens, the AG genotype had higher AFE than that of the GG genotype ( p  < 0.05).